2019
DOI: 10.5812/ijp.86450
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis of Early Fetal Cardiac Changes of the Gestational Diabetic Mothers: Presenting the Preload Index

Abstract: Objectives: To evaluate fetal cardiac changes in gestational diabetic mothers, compared to healthy ones by means of different indices and to determine which index can first represent the alterations. Methods: The study was conducted as an observational cross-sectional study, including 25 pregnant women with gestational diabetes as the cases and 50 healthy pregnant women as the controls. The preload index, left and right side myocardial performance index (MPI), Interventricular septal hypertrophy, the left and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…As both outcome measures were relevant for this review, we included both studies but handled them as a single study. Hence, a total of 39 studies met the inclusion criteria and were included in this review (Figure 1) 11–13,25–61 . Of these, 31 studies reported data on IVS thickness, E/A ratio and/or MPI and were included in the meta‐analysis 11,12,25–28,30–36,38,39,41,42,45–53,55–60 .…”
Section: Resultsmentioning
confidence: 99%
“…As both outcome measures were relevant for this review, we included both studies but handled them as a single study. Hence, a total of 39 studies met the inclusion criteria and were included in this review (Figure 1) 11–13,25–61 . Of these, 31 studies reported data on IVS thickness, E/A ratio and/or MPI and were included in the meta‐analysis 11,12,25–28,30–36,38,39,41,42,45–53,55–60 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, left fetal MPI values were reported as median and interquartile range, and we were not able to contact the authors for further data. The study from Patey et al was excluded because left fetal MPI values were reported as median and interquartile range, and we were not able to contact the authors for further data [34]. We were able to contact Dr. Ismail Bhorat, who provided us with unpublished data for 3 studies [27,31,33].…”
Section: Study Selectionmentioning
confidence: 99%
“…737 studies remained after removal of duplicates, and 78 after screening of titles. Lastly, sixteen articles were assessed for eligibility after screening of abstracts [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations